Use Of Word And Syllables Among Students In Modern Time Through Social Media - Surayya, Azizah; Zahra , Mutia; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
English /1/ has traditionally been classified into at least two allophone, the easier syllable that usually comes first, and dark, which is a syllable finally . As he found out the vowel /1/s preceding the possible phonetic boundary phonetic between the two extremes, most researchers have end to assume that allophones of phonemes are categorical different elements. This article introduces acoustics and X-rays microbeam data for English /1/, before and before phonological boundary, in relation to /i - 1/. Main the degree of light-dark contrast of the articulations appears as follows: (1) greater retraction and lowering of the tongue for a darker back variant of /I/; (2) earlier occurrence in the darker version of /1/ dorsal retraction and lowering of the limb relative to the apical extreme improvement over easier timing version /1/ in which the hind limb is slower than apex extremity. It can also be seen that the darkness of /1/ is a with the above articulation steps and formant frequencies action - strongly correlated with measured acoustics the duration of rhymes containing the prefix /1/. We interpret our results as evidence that there is no reason for treatment light and dark allophones are phonologically categorically different (or phonetic) entities in English. Instead, phonological singular the entity /1/ is phonetically realized as a lighter or darker variant depending on factors such as the position of /1/ in the syllable, and the phonetic duration of the prosodic context containing /I/. it is suggested that /1/s contains back vowel movement as well as a consonant peak motion. We recommend that the vocal movement have a strong affinity for the core syllable, while for the consonant movement has a strong affinity for margin. Two gestures from: /1/ so basically asynchronous sound movements come through the last syllable before it (ie the /1/s closest to the dot). Consonant sign, and the reverse situation remains iinitial syllable /1/s. For this explanation to work, phonetics the implementation must have access to the information within the syllable the position of phonological elements. We will talk about it most of the correlation is caused by the coarticulation of the underdrive